2014
DOI: 10.1002/ldr.2326
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐Economic Determinants of Adoption of Rainwater Harvesting and Conservation Techniques in Semi‐Arid Tharaka Sub‐County, Kenya

Abstract: This paper examines determinants of adoption of rainwater harvesting and conservation techniques in semi-arid Tharaka sub-county, Eastern Kenya. Given the erratic rainfall that characterises Tharaka, rainwater harvesting and conservation is critical for the improvement of agricultural production. The study was conducted in two agro-ecological zones, and 196 respondents were interviewed. The majority of the farmers were practising between 1-3 and 4-6 rainwater harvesting and conservation techniques-an indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
0
31
1
Order By: Relevance
“…An additional layer of difficulty is being imposed by increasing rates of land degradation, which negatively impacts the growth of agriculture worldwide (Wingeyer et al, ). There are many factors such as vegetation loss, soil erosion, improper water management, and wrong agricultural practices that are responsible for land degradation (Baumert, Khamzina, & Vlek, ; Recha, Mukopi, & Otieno, ). Besides, contaminating agents including salt, heavy metals, and effluents from textile industries also contribute to land degradation and subsequent loss in crop production.…”
Section: Introductionmentioning
confidence: 99%
“…An additional layer of difficulty is being imposed by increasing rates of land degradation, which negatively impacts the growth of agriculture worldwide (Wingeyer et al, ). There are many factors such as vegetation loss, soil erosion, improper water management, and wrong agricultural practices that are responsible for land degradation (Baumert, Khamzina, & Vlek, ; Recha, Mukopi, & Otieno, ). Besides, contaminating agents including salt, heavy metals, and effluents from textile industries also contribute to land degradation and subsequent loss in crop production.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these systems are actually not operating as well as expected [7] and it is thus very important to determine decisive factors influencing this in Beijing. In the literature, there are studies in discussing determinants of RWHs [11][12][13], which mostly pursue to find the factors influencing the adoption of RWHs. While, this study emphasizes to prove that non-technological factors are as substantial as technological factors in the successful management of RWHs via the identification of decisive factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on farmer's perceptions found that farmers' behaviour may be primarily driven by short‐term economic implications and that they discount long‐term losses associated with land degradation (Kerr & Pender, ). Farmer's adoption of soil management strategies was affected by socio‐economic determinants (Recha, Mukopi, & Otieno, ). Therefore, for both soil protection and adaptation after land degradation occurs, it is critical to take into account farmers' short‐term economic drivers.…”
Section: Discussionmentioning
confidence: 99%